2020
DOI: 10.1017/s0263574720000235
|View full text |Cite
|
Sign up to set email alerts
|

Improved Motion Planning of Humanoid Robots Using Bacterial Foraging Optimization

Abstract: SUMMARY This paper emphasizes on Bacterial Foraging Optimization Algorithm for effective and efficient navigation of humanoid NAO, which uses the foraging quality of bacteria Escherichia coli for getting shortest path between two locations in minimum time. The Gaussian cost function assigned to both attractant and repellent profile of bacterium performs a major role in obtaining the best path between any two locations. Mathematical formulations have been performed to design the control architecture for huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Moreover, the technology of deep learning [43][44][45][46] should also be considered to build machine aesthetic models. Furthermore, some advanced motion planning algorithms of humanoid robots [47,48] will be helpful to generate robotic dance motions quickly, avoid robots falling to a certain extent, and finally enrich the construction of the dataset of robotic dance motions. These open questions will be explored in the future.…”
Section: Limitation Of the Proposed Approachmentioning
confidence: 99%
“…Moreover, the technology of deep learning [43][44][45][46] should also be considered to build machine aesthetic models. Furthermore, some advanced motion planning algorithms of humanoid robots [47,48] will be helpful to generate robotic dance motions quickly, avoid robots falling to a certain extent, and finally enrich the construction of the dataset of robotic dance motions. These open questions will be explored in the future.…”
Section: Limitation Of the Proposed Approachmentioning
confidence: 99%
“…It may be seen in the prey behavior of social insects, the navigation of herds of birds, and the careful activity of fishes.Swarm intelligence refers to an animal's collective and self-organizing behavior. Several publications have employed bio-inspired methodologies to tackle various parts of path planning strategies [1][2][3][4][5][6][7][8][9], a Whale Optimization Algorithm (WOA), applied in fixed situations to meet prerequisites for the optimization length of the path and smoothing path [10,11], and Dai et al [12], suggested a method that based on the Cuckoo Optimization Algorithm for planning the robot's path in a moving situation.…”
Section: Introductionmentioning
confidence: 99%
“…The goals of optimization involved are the length of the path, the degree of evenness and the degree of safety of the route. Muni et al (2020a, 2020b, 2020c, 2020d, 2021) have proposed the hybrid artificial intelligent technique for control over humanoid robots. Kumar et al (2020a, 2020b, 2021) have proposed hybrid sine cosine and ACO technique path planning of mobile robot.…”
Section: Introductionmentioning
confidence: 99%
“…The goals of optimization involved are the length of the path, the degree of evenness and the degree of safety of the route. Muni et al (2020aMuni et al ( , 2020bMuni et al ( , 2020cMuni et al ( , 2020dMuni et al ( , 2021 have proposed the hybrid artificial intelligent technique for control over humanoid robots. Kumar et al (2020aKumar et al ( , 2020bKumar et al ( , 2021 Several techniques studied in the literature survey are already proposed by the researchers concerning navigational problems of the mobile robot, but no one confirms the generated path is optimal or not.…”
mentioning
confidence: 99%